Determination of Operation Factors in Treating Piggery Wastewater by Membrane Bioreactor - Nguyễn, Sáng (ĐHQGHN, 2015)
An investigation into the treatment efficiency of real piggery wastewater of a bench-scale aerobic membrane bioreactor was performed. The experiments were aimed to evaluate the effects of hydraulic retention time and activated sludge concentration. The piggery wastewater having high chemical oxygen demand, ammonium and total phosphorus concentrations (about 4200 mg/l, 320 mg/L and 48 mg/L, respectively) was employed. It was found that the removal efficiency of COD reached up to 94% even at operation conditions of HRT = 24 hours and MLSS = 6000 mg/L, but the HRT need to be increased twice in order to obtain the removal of 99% NH4+-N and 85% T-P. The similar efficiency was also achieved by reduced HRT to 8 hours but increased MLSS to 12000 mg/L. Keywords: Membrane bioreactor (MBR), piggery wastewater, microfiltration, activated sludge, eutrophication.